PUBLIC ATTITUDE TOWARDS THE PEACEFUL NUCLEAR EXPLOSIONS CONDUCTED IN THE REPUBLIC OF SAKHA (YAKUTIA) - G. V. Arkhangelskaya; T. A. Vasilieva; S. A. Zelentsova; A. Yu. Medvedev; V. P. Ramzaev; M. A. Timofeeva (Радиационная гигиена)
The paper contains a brief summary on radiation situation in the region of the peaceful nuclear explosions (PNE) «Crystal» and «Kraton-3» as well as original assessments of public attitude towards the PNEs and the countermeasures that had been done at the sites of these explosions in the past. Results of the public-opinion poll, which has been conducted in the settlements of Aikhal, Udachny, Malgajar, Zharkhan and Malykhay in 2010, are presented. For the data collection, specially designed anonymous questionnaire was used. Totally 144 adult respondents participated in the survey. About 19% of the respondents had visited the sites of PNE with different aims and in different periods. The majority (70-80%) of the respondents believes that the PNEs, which were carried out in Yakutia in the last century, are the main source of radioactive contamination in the area of their settlements. Only a half of the respondents consider that some countermeasures have been applied at the sites of these PNEs.